Proposed quick method for applying dynamic lane assignment at signalized intersections - Khaled J. Assi; Nedal T. Ratrout (IATSS Research, 2018)
Almost all researches about dynamic lane assignment were conducted to evaluate the effectiveness of applying this technique at signalized intersections. However, little attention was given to the method of identifying quickly the optimum lane group. This research suggests a quick method to find the optimum lane group for 3-lane and 4-lane approaches at junctions where each approach has green by itself in turn using the percentage of turning movements. MATLAB environment was used to build an optimization model to find the optimal lane groups at all intersection approaches for hypothetical massive traffic demand combinations using an objective function of minimizing intersection delay. This finding represents a plausible quick method to predict the optimum lane group in the field instantaneously using the percentage of turning movements at the approach without conducting massive calculations. Keywords: Signalized intersection, Dynamic lane assignment, Optimum lane grouping, Pre-timed signal, Optimization model